2019
DOI: 10.1182/bloodadvances.2018026054
|View full text |Cite
|
Sign up to set email alerts
|

Critical role of Jumonji domain of JMJD1C in MLL-rearranged leukemia

Abstract: JMJD1C, a member of the lysine demethylase 3 family, is aberrantly expressed in mixed lineage leukemia (MLL) gene-rearranged (MLLr) leukemias. We have shown previously that JMJD1C is required for self-renewal of acute myeloid leukemia (AML) leukemia stem cells (LSCs) but not normal hematopoietic stem cells. However, the domains within JMJD1C that promote LSC self-renewal are unknown. Here, we used clustered regularly interspaced short palindromic repeats (CRISPR)/CRISPR-associated protein-9 nuclease (Cas9) neg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
19
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 61 publications
4
19
1
Order By: Relevance
“…Moreover, we found that the expression level of KDM3C was higher in M3 patients in comparison with other subtypes of AML. Previous reports have suggested that via regulation of IL-3/RAS/JAK pathway and also through cooperation with the HOXA9/MEIS1 axis, KDM3C could exert pro-oncogenic function in AML [47]. On the other hand, in contrast to Oncomine databases, which assigned an elevated expression of KDM2B in acute leukemias, we found a normal expression for this gene in the AML patients [19].…”
Section: Discussioncontrasting
confidence: 88%
“…Moreover, we found that the expression level of KDM3C was higher in M3 patients in comparison with other subtypes of AML. Previous reports have suggested that via regulation of IL-3/RAS/JAK pathway and also through cooperation with the HOXA9/MEIS1 axis, KDM3C could exert pro-oncogenic function in AML [47]. On the other hand, in contrast to Oncomine databases, which assigned an elevated expression of KDM2B in acute leukemias, we found a normal expression for this gene in the AML patients [19].…”
Section: Discussioncontrasting
confidence: 88%
“…KG‐1 harbors NRAS mutation, P15INK4B methylation, P16INK4A methylation, P53 mutation, RB1 rearrangement and modest JMJD1C expression. One study showed that Ras mutations confer resistance to JMJD1C depletion . However, THP‐1 that harbors MLL‐AF9 fusion, NRAS mutation, P15INK4B deletion, P16INK4A deletion, P53 mutation, RB1 rearrangement and robust JMJD1C expression is also sensitive to JMJD1C depletion and JDI‐4/JDI‐12/JDI‐16 treatment.…”
Section: Discussionmentioning
confidence: 99%
“…One study showed that Ras mutations confer resistance to JMJD1C depletion. 32 However, THP-1 that harbors MLL-AF9 fusion, NRAS mutation, P15INK4B deletion, P16INK4A deletion, P53 mutation, RB1 rearrangement and robust JMJD1C expression is also sensitive to JMJD1C depletion and JDI-4/JDI-12/JDI-16 treatment. It seems possible that both the Ras mutation and MLL rearrangement confers resistance to JMJD1C depletion.…”
Section: Discussionmentioning
confidence: 99%
“…Only ~1% of fusion protein binding sites are shared across leukemia samples, and these shared sites represent 6% of total sequence space (506kb/8377kb) bound by KMT2Ar in any cell type (Supplementary Table 2). The group of 15 genes that is targeted by the fusion protein in all KMT2Ar leukemia samples is highly enriched for master regulators of hematopoiesis as well as genes that are required for KMT2Ar leukemia [24][25][26][27][28] Table 2).…”
Section: A Strategy For Mapping the Binding Sites Of Diverse Kmt2a Fumentioning
confidence: 99%